Comparison of three semi-analytical methods for solving (1+1)-dimensional dispersive long wave equations - Ugurlu, Yavuz; Kaya, Dogan; Inan, Ibrahim E. (Pergamon-Elsevier Science Ltd, 2011)
In this work, we consider how Adomian's decomposition method (ADM), the homotopy analysis method (HAM) and the homotopy perturbation method (HPM) can be used to investigate wave solutions of (1 + 1)-dimensional dispersive long wave equations. It is also worth noting that the advantage of the approximation of the series methodologies is a fast convergence of the solutions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Adomian's decomposition method; Homotopy analysis method; Homotopy perturbation method; (1+1)-dimensional dispersive long wave equation; Semi-analytical methods; Series solutions; Adomian polynomials